The role of the MTHFR C677T polymorphism in methotrexate-induced toxicity in pediatric osteosarcoma patients. (June 2017) - Lambrecht, Loes; Sleurs, Charlotte; Labarque, Veerle; Dhooge, Catharina; Laenen, Annouschka; Sinnaeve, Friedl; Renard, Marleen; Uyttebroeck, Anne
Aim: Osteosarcoma patients receive high doses of methotrexate (MTX). However, pharmacogenetic information remains limited and has mainly been investigated in leukemia so far.Patients & methods : We investigated the link between the MTHFR C677T genotype, toxicity levels (mucositis, MTX plasma level, hematological toxicity and hepatotoxicity) and survival of 48 pediatric osteosarcoma patients.Results: The TT genotype did not show more toxicity compared with the CC/CT genotype. However, plasma MTX levels were related with mucositis, but not with hematological toxicity, nor hepatotoxicity. Survival rates did not differ between homozygous and non-homozygous patients. Yet, homozygous patients had higher relapse risk.Conclusion: The MTHFR C667T polymorphism is not predictive for toxicity or overall survival, but could be used for relapse risk stratification.